The value proposition of Islamic Financial intermediation: some current legal and regulatory challenges - Oseni, Umar Aimhanosi; Kadouf, Hunud Abia; Ansari, Abdul Haseeb; Olayemi, Abdul Azeez Maruf (AENSI Publications, 2012)
Abstract: With the tremendous growth experienced in the Islamic finance industry within the past decade, there is an increasing call for self-evaluation in order to reemphasize the need to realize original value proposition of Islamic financial intermediation in Islamic commercial law. The Islamic finance industry has been criticized by some skeptics that it has skid off the track of its original trajectory envisioned by its pioneers. This paper therefore examines some current legal and regulatory challenges in identifying the original value proposition of Islamic financial intermediation in the modern Islamic finance industry. As an exploratory study, this paper identifies a number of legal and regulatory reforms necessary to reposition the global Islamic finance industry in order to make it more conventionally viable without compromising the fundamentals of Sharī'ah. The paper concludes with the need to rekindle the original value proposition of Islamic finance, particularly in countries where Islamic finance is just gaining grounds. It is always good to get things right at the initial stage to avoid some sort of legal and regulatory transplants that are not adaptable to such jurisdictions. Key words: Islamic finance, law, value proposition, Islamic financial intermediation.